Исследование показателей гемодинамики в сосудах матки при лейомиоме у женщин репродуктивного возраста = Hemodynamics indexes in the vessels of uterus at leiomyoma in the women of fertile age - M. B. Zaporozhchenko (Kazimierz Wielki University, 2015)
Zaporozhchenko M. B. Исследование показателей гемодинамики в сосудах матки при лейомиоме у женщин репродуктивного возраста = Hemodynamics indexes in the vessels of uterus at leiomyoma in the women of fertile age. Journal of Education, Health and Sport. 2015;5(6):297-303. ISSN 2391-8306. DOI 10.5281/zenodo.18616 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A297-303 https://pbn.nauka.gov.pl/works/566852 http://dx.doi.org/10.5281/zenodo.18616 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015.   УДК 618.14-006.363.03:612.13   Исследование показателей ГЕМОДИНАМИКИ в сосудах матки при лейомиоме У ЖЕНЩИН РЕПРОДУКТИВНОГО ВОЗРАСТА   Hemodynamics indexes in the vessels of uterus at leiomyoma in the women of fertile age   М. Б. Запорожченко M. B. Zaporozhchenko   Одесский национальный медицинский университет Odessa National Medical University, Odessa, Ukraine   Abstract Urgency. Frequency of uterine leiomyoma is up to 60% in the overall structure of gynecological diseases. Objective: to assess the state of regional hemodynamics in women with uterine leiomyoma. Materials and methods. Regional hemodynamics was studied in blood vessels of the uterus in 120 women of reproductive age with leiomyoma and uterine fibroids. We studied the blood flow in the uterine, arcuate, ovarian arteries and the myometrium; intratumoral and peritumoral blood flow depending on the location and vascularization node histological structure and phase of the menstrual cycle. Doppler of uterine and intratumoral blood flow helped to clarify the morphological structure of the tumor, the risk of its "rapid growth" and to determine medical tactic. Features of uterine and intratumoral blood flow may be used as an additional indicator in the diagnosis of morphofunctional state of organ and tumor. It is advisable to conduct further in-depth study of the pathogenetic mechanisms of uterine leiomyoma using the methods of ultrasound diagnostics. Keywords: uterine leiomyoma, uterine blood flow, intratumoral blood flow, Doppler.   Реферат Актуальность. Частота лейомиомы матки составляет до 60% в общей структуре гинекологических заболеваний. Цель исследования: провести оценку состояния региональной гемодинамики у женщин с лейомиомой матки. Материалы и методы. Региональная гемодинамика исследована в сосудах матки у 120 женщин репродуктивного возраста с лейомиомой и фибромой матки.  Изучали кровоток в маточных, аркуатных, яичниковых артериях и миометрии; внутриопухолевый и перитуморальный кровоток в зависимости от расположения и васкуляризации узла, гистологической структуры и фазы менструального цикла. Допплерометрия маточного и внутриопухолевого кровотока позволила уточнить морфологическую структуру опухоли, риск ее «быстрого роста» и определить врачебную тактику. Особенности маточного и внутриопухолевого кровотока возможно использовать в качестве дополнительного показателя в диагностике морфофункционального состояния органа и опухоли. Целесообразно провести дальнейшее углубленное изучение патогенетических механизмов возникновения лейомиомы матки с применением методов ультразвуковой диагностики. Ключевые слова: лейомиома матки, маточный кровоток, внутриопухолевый кровоток, допплерометрия.